Cerebral aspergillosis and facial acneiform lesions following initiation of ibrutinib in a patient with chronic lymphocytic leukemia. (2021) - Bedier, Helbies; Lin, John; Frenette, Charles; Routy, Jean-Pierre
Abstract: A case of a 67-year-old male with CLL, presented with prolonged pancytopenia after his first cycle of fludarabine, cyclophosphamide, and rituximab (FCR) chemotherapy. He was then treated with ibrutinib oral monotherapy. Shortly after ibrutinib treatment initiation, he developed a brain abscess and pulmonary disease as a part of an invasive aspergillosis. The patient improved after brain abscess drainage and the anti-fungal therapy voriconazole. Upon resuming ibrutinib four months after his hospitalization, he developed extensive acneiform facial lesions. This case is the first to report on the development of two separate complications in one patient related to ibrutinib, namely, Aspergillus infection, and severe acneiform skin lesions.